Success of a low‐sloping rack for improving downstream passage of silver eels at a hydroelectric plant. (25th July 2013) - Calles, O.; Karlsson, S.; Vezza, P.; Comoglio, C.; Tielman, J.
Summary: The European eel ( Anguilla anguilla ) is a critically endangered species, and one major threat is the survival of silver eels migrating downstream towards the sea from lake and river rearing areas. During this migration, many eels are impinged and die on intake racks, or are injured or killed when passing through turbines. Intake racks at a hydroelectric plant were modified to avoid impingement and to collect eels without injury; high mortality on both racks and in turbines was previously documented. Modifications consisted of reducing the rack gap width from 20 to 18 mm, decreasing the rack slope from 63 to 35 degrees, increasing the rack surface area by 58% and installing six openings in the rack leading to traps. Downstream passage conditions for silver eels at the hydroelectric plant were significantly improved, reducing mortality from >70% at the old steep 20 mm racks to <10% at the modified 18 mm rack collection facility. No tagged eels were impinged and killed on the racks, and 80% entered the collection facility. Survival can probably be improved even more, as the individuals that passed the facility most likely escaped through holes in the traps. Moreover, injured untagged eels were still encountered at the modified racks, illustrating the need for rehabilitative measures to be implemented at all obstacles between the main eel rearing areas and the sea.